A Novel Ratiometric Fluorescent Probe for Mercury (II) ions and Application in Bio-imaging - Qianmiao Gao (Molecules, 2019)
Since the accumulation of mercury (II) ions in the environment and ecosystem causes serious problems to environment and disease, the recognition of Hg2+ ions and its bio-imaging is of high importance. In sight of the advantages of fluorescence probes, a new probe (PMH) was facilely synthesized by incorporating phenylimidazole fluorophore and 3-methyl-2- benzothiazolinone hydrazone hydrochloride monohydrate. The PMH probe exhibited a ratiometric response for Hg2+ ions with fluorescence intensity increasing at 520 nm and decreasing at 445 nm simultaneously. The PMH probe interacted with Hg2+ ions in seconds with high optical stability and showed good selectivity over other metal ions. In addition, the probe has excellent biocompatibility and imaging performance in cells and zebrafish.